Subjective and objective limits of tapping in criminal proceedings (Ius Novum, 2019)
The article discusses the subjective and objective scope of tapping in criminal proceedings. To that end, the author analyses the provisions of the Code of Criminal Procedure in relation to interception and the recording of communications. The issue of admissibility of applying such a coercive measure is strictly linked with giving consideration to the protection of interests of the administration of justice and to the possibility of interference into the privacy of an individual. Under this thesis, the article aims to balance the contradictory interests so that a compromising solution can be found. It is particularly apparent with respect to the controversial and complex issue of the extension of the limits of tapping. In this scope, the amendments to the Criminal Procedure Code introduced by the Act of 4 February 2011 and by the Act of 11 March 2016 have been analysed and new amendments have been proposed. The opinion is herein presented that going beyond the subjective and objective limits set forth in the relevant court’s decision without a court’s consent should not be admissible.
Keywords: tapping; right to privacy; subjective and objective limits; criminal proceedings; court’s consent